2017
DOI: 10.7448/ias.20.7.21780
|View full text |Cite
|
Sign up to set email alerts
|

Understanding low sensitivity of community‐based HIV rapid testing: experiences from the HPTN 071 (PopART) trial in Zambia and South Africa

Abstract: Introduction: Population-wide HIV testing services (HTS) must be delivered in order to achieve universal antiretroviral treatment (ART) coverage. To accurately deliver HTS at such scale, non-facility-based HIV point-of-care testing (HIV-POCT) is necessary but requires rigorous quality assurance (QA). This study assessed the performance of community-wide HTS in Zambia and South Africa (SA) as part of the HPTN 071 (PopART) study and explores the impact of quality improvement interventions on HTS performance. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported more than one unit of measure, and three studies did not specify sample size (see supplementary information). The majority of studies occurred in a facility-based setting; studies carried out in community settings included the workplace ( n  = 1) [57], home-based testing ( n  = 2) [14,39] and a mobile setting ( n  = 1) [32]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations